A Rediscovery of Voice: The Story of Self Through a Qualitative Lens (LEARNing Landscapes, 2018)
The following article tells the story of how a qualitative research methods PhD course and the creation of a researcher portfolio helped to answer the sometimes elusive question of, “Who am I as a researcher?” and ultimately led to a rediscovery of voice. This story describes how using various modes of inquiry set the groundwork for my rediscovery of voice. This is my story. This is my story about voice. This is my story about how this PhD course provided the starting point to discover who I was as a researcher, and, more importantly, allowed me to reclaim my lost voice.
Keywords: qualitative research and voice; arts-based research methodologies; teaching and learning qualitative research